Une ferme seigneuriale au XIVe siècle La grange du Mont (Charny, Côte-d'Or) - Beck, Patrice (Documents d'archéologie française, 1989)
Settled at the end of the XIIIth century on an unexploited land of the seignory of Mont-Saint-Jean, in Auxois, the "grange du Mont" was abandoned a hundred years later ; it did not resist to the demographic and economie recession at the end of the XIVth century, although it had been built to farm a large territory in a permanent way, as shown by the size and the quality of the structures. The archaeological excavation, the study of the archives and the ethnographic research, associated in an exemplary way, have led to the reconstitution of the structure and aims of such an agro-pastoral settiement in the Middle Age conception. This study brings new informations about a type of farming settiement poorly known until now, the "grange", as well as about the artefacts and architecture of the rural settlements in mediaeval Burgundy.